Therapeutic-dose heparin combined with antiplatelets in noncritically ill patients with COVID-19: a secondary analysis of a multiplatform randomized controlled trial - Sylvain A. Lother; Wen Teng; Olawale Ayilara; Brett L. Houston; Barret Rush; Srinivas Murthy; Jose C. Nicolau; Lindsay Bond; Alexis F. Turgeon; John C. Marshall; Jonathan Paul; Judith S. Hochman; et al. (Research and Practice in Thrombosis and Haemostasis)
Background: Therapeutic-dose heparin improves outcomes in noncritically ill patients hospitalized for COVID-19. The effect of antiplatelet exposure in addition to therapeutic-dose heparin is unknown. Objectives: To evaluate the effect of antiplatelet exposure in addition to therapeutic-dose heparin on survival without organ support. Methods: We conducted an observational secondary analysis of a multiplatform randomized controlled trial, analyzing noncritically ill patients hospitalized for COVID-19 who received an antiplatelet agent (acetylsalicylic acid or P2Y12 inhibitor) and therapeutic-dose heparin (combination) compared with therapeutic-dose heparin alone (control). We used a 3-level ordinal primary outcome: (1) survival without organ support, (2) survival with organ support, and (3) mortality by day 21. Propensity scores were estimated using logistic regression. Balanced analytic groups were established using stabilized inverse probability of treatment weighting. A proportional odds model was used to estimate the effect of antiplatelet exposure. Results: Among 1021 patients, 194 (19.0%) were exposed to an antiplatelet (95.4% acetylsalicylic acid) and therapeutic-dose heparin. All patients were used to calculate the propensity scores and stabilized weights. After applying inverse probability of treatment weighting, the effective sample size was 60 in the combination group and 652 in the control group. Means and prevalences of continuous and dichotomous variables were similar between groups, with no evidence of misclassification. Exposure to an antiplatelet was not associated with improved survival without organ support (76.3% vs 80.5%; odds ratio, 1.07; 95% CI, 0.71-1.64). Conclusion: In noncritically ill patients hospitalized for COVID-19 receiving therapeutic-dose heparin, exposure to an antiplatelet agent was not associated with improved survival without organ support.